2014
DOI: 10.1007/s00280-014-2648-9
|View full text |Cite
|
Sign up to set email alerts
|

A multi-institution phase II study of gemcitabine/cisplatin/S-1 (GCS) combination chemotherapy for patients with advanced biliary tract cancer (KHBO 1002)

Abstract: Gemcitabine/cisplatin/S-1 combination chemotherapy offered a promising survival benefit with manageable toxicity in patients with advanced BTC. A randomized phase III trial to investigate the efficacy of this regimen compared to gemcitabine/cisplatin combination therapy in patients with advanced BTC is now underway (UMIN000014371/NCT02182778).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 26 publications
0
40
0
Order By: Relevance
“…A phase II study demonstrated significantly prolonged MST (16.2 months, 95% confidence interval 10.2–22.2 months) without uncontrollable adverse events compared with that of the ABC-02 study (11.7 months, hazard ratio = 0.64; P<0.001). Interestingly, two patients (4%) were able to achieve curative secondary resection after tumor downstaging following chemotherapy (8). Thus, GCS combination therapy should not only be considered to be a standard first-line chemotherapy, but also a ‘conversion surgery or neoadjuvant chemotherapy’.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A phase II study demonstrated significantly prolonged MST (16.2 months, 95% confidence interval 10.2–22.2 months) without uncontrollable adverse events compared with that of the ABC-02 study (11.7 months, hazard ratio = 0.64; P<0.001). Interestingly, two patients (4%) were able to achieve curative secondary resection after tumor downstaging following chemotherapy (8). Thus, GCS combination therapy should not only be considered to be a standard first-line chemotherapy, but also a ‘conversion surgery or neoadjuvant chemotherapy’.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kanai et al determined the optimal dose of GC/S-1 (GCS) combination therapy for patients with advanced BTC in a phase I study (7) and reported a promising MST of >15 months in a phase II study (8). Based on these results, a phase III randomized trial is underway to demonstrate the superiority of GCS therapy compared with GC in patients with unresectable BTC (UMIN000014371/NCT02182778).…”
Section: Introductionmentioning
confidence: 99%
“…In previous phase I and II studies, a biweekly schedule of GPS combination therapy has already been evaluated in ABTC patients . However, the dose in the biweekly regimen may not have reached the maximum tolerated dose in the previous phase I study.…”
Section: Discussionmentioning
confidence: 99%
“…Several phase I and II studies have evaluated the effectiveness of gemcitabine with platinum and FU in ABTC patients . The main grade 3 or higher toxicities were neutropenia (24–32%) and thrombocytopenia (7–33%), and a few grade 3 or higher non‐hematological toxicities were reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation